Penerapan Model Pembelajaran Problem Based Learning dipadu Media Animasi untuk Meningkatkan Keterampilan Proses Sains, Motivasi dan Hasil Belajar Biologi di SMAN Aceh Utara - Salfina Salfina; Cut Nurmaliah; Andi Ulfa Tenri pada; Hasanuddin Hasanuddin; Abdullah Abdullah (Postgraduate, University of Mataram, 2021)
This study aims to determine the application of problem-based learning models combined with animation media that can improve students' learning science process skills. The method used in this research is an experiment with a pretest-posttest control group design. This research was conducted at two senior high schools in North Aceh Regency, Aceh, Indonesia. The study was conducted in the even semester of the 2020/2021 Academic Year. The research sample was taken by random sampling of 102 students, namely the experimental group 51 and the control group 51. The parameter measured in the study was the students' science process skills. The data of science process skills were analyzed by parametric statistical test independent sample t-test. The results showed that there was an increase in science process skills after being taught using a problem-based learning model combined with animation media. The conclusion of this study is that the application of problem-based learning models combined with animation media can improve students' science process skills on the sensory system material at SMAN 1 Meurah Mulia and SMAN 1 Tanah Pasir.